2009
DOI: 10.1073/pnas.0901643106
|View full text |Cite
|
Sign up to set email alerts
|

Climatic extremes improve predictions of spatial patterns of tree species

Abstract: Understanding niche evolution, dynamics, and the response of species to climate change requires knowledge of the determinants of the environmental niche and species range limits. Mean values of climatic variables are often used in such analyses. In contrast, the increasing frequency of climate extremes suggests the importance of understanding their additional influence on range limits. Here, we assess how measures representing climate extremes (i.e., interannual variability in climate parameters) explain and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
304
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 332 publications
(311 citation statements)
references
References 72 publications
6
304
0
1
Order By: Relevance
“…Epistemic uncertainty as a limited knowledge about tree species response to extreme drought remains high compared with better knowledge about average drought impacts in British conditions. A recent study by Zimmermann et al (2009) highlighted the need for information about climate extremes that can improve our understanding of species limits and support robust estimations of species distributions. Extreme droughts are more damaging, affect forest productivity (Ciais et al 2005), and are projected to become more frequent in the future (Meehl and Tebaldi 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Epistemic uncertainty as a limited knowledge about tree species response to extreme drought remains high compared with better knowledge about average drought impacts in British conditions. A recent study by Zimmermann et al (2009) highlighted the need for information about climate extremes that can improve our understanding of species limits and support robust estimations of species distributions. Extreme droughts are more damaging, affect forest productivity (Ciais et al 2005), and are projected to become more frequent in the future (Meehl and Tebaldi 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Current forecasting approaches that produce future climate averages may make it difficult to detect non-linear ecosystem dynamics, or threshold effects, that could trigger abrupt ecosystem change (Campbell et al 2009). Zimmermann et al (2009) found that predictions of spatial patterns of tree species in Switzerland were improved by incorporating measures of extremes in addition to means in SDMs.…”
Section: Species Responses To Climatementioning
confidence: 99%
“…To evaluate the correlation between multicharacter differences among populations, a Mantel test (Mantel 1967) was performed on the matrices of Euclidean distances. First, the correlations among all 19 WorldClim bioclimatic variables and topographic variables for all presence points were calculated to exclude the highly correlated ones, whilst keeping the variables useful in predicting the distribution limits of trees, such as climatic averages and extremes (Zimmermann et al 2009;Temunović et al 2012). We computed and tested the correlations between: (1) the matrix of the geographical distances between pairs of populations and the matrix of morphological differences among populations -"isolation by distance" (Wright 1943); and (2) the matrix of environmental distances and the matrix of morphological differences among populations -"isolation by environmental distance" (Mendez et al 2010).…”
Section: Statistical Analyses -Statističke Analizementioning
confidence: 99%